AB0267 Treatment paradigms in real-world practice: biologic agent use prior to and after discontinuation of abatacept in the action study. (15th June 2017) - Alten, R; Lorenz, H-M; Mariette, X; Nüßlein, H; Galeazzi, M; Navarro, F; Chartier, M; Elbez, Y; Rauch, C; Bars, M Le
Abstract : Background: ACTION is a 2-year, observational study of patients (pts) with moderate-to-severe RA who initiated IV abatacept (ABA) in Canada and Europe (NCT02109666 ). Objectives: To determine pt biologic (b)DMARD use prior to initiation and after discontinuation of ABA overall and by treatment line in ACTION. Methods: Pts with RA initiated IV ABA as first- or second-/further-line therapy. Biologic-naïve and biologic-failure pts were enrolled during three periods between May 2008 and December 2013. Pts could switch administration routes (IV to SC) during treatment. Crude retention rates (Kaplan–Meier) were compared by log-rank test. Results: Of the 2364 pts enrolled, 2350 were evaluable for analysis: 673 (28.6%) were biologic naïve and 1677 (71.4%) biologic failures. Baseline characteristics differed: biologic-failure pts had longer RA duration, higher CRP levels and prevalence of radiographic erosions, and lower rates of chronic obstructive pulmonary disease and neoplasms vs biologic-naïve pts. Most biologic-failure pts (96.7%) had previously received ≥1 TNF inhibitor (TNFi): 48.7% had received 1 and 48.0% ≥2 TNFi; 56.6% had received ≥2 bDMARDs. The overall 2-year retention rate was 47.9% and was higher for biologic-naïve vs biologic-failure pts (54.5 vs 45.2%; p<0.001); the most common reasons for ABA discontinuation were inefficacy (61.4 vs 67.7%) and safety (21.3 vs 21.2%). In pts who discontinued ABA, 83.0% started a bDMARD ≤6 months after discontinuation (Table), most commonly ABA IV. Mean (SD) days from stopping ABA to starting a bDMARD was similar for biologic-naïve (93.4 [51.3]) and biologic-failure pts (93.6 [48.0]). Among pts who restarted ABA, 62 (80.5%) biologic-naïve and 158 (85.0%) biologic-failure pts were considered to have discontinued as the time from last dose was >84 (IV) or >28 (SC) days, and thus were no longer temporary discontinuations, as predefined in the protocol. Three pts discontinued for bad compliance, 3 for lack of efficacy, 3 for remission/major improvement, 12 for safety and 15 for surgery. A good/moderate EULAR response was achieved by 76.7% of pts at the last follow-up before ABA discontinuation and 58.3% at ABA restart; mean (SD) DAS28 (CRP) was 3.2 (1.1) and 3.8 (1.4), respectively. Conclusions: Prior to abatacept treatment, over half of biologic-failure pts had received ≥2 bDMARDs and most had received a TNFi. After initial discontinuation (protocol defined), over one-third of pts restarted abatacept. Disclosure of Interest: R. Alten Grant/research support from: Bristol-Myers Squibb, Speakers bureau: Bristol-Myers Squibb, H.-M. Lorenz Consultant for: AbbVie, Bristol-Myers Squibb, Roche-Chugai, UCB, MSD, GSK, SOBI, Medac, Novartis, Janssen-Cilag, AstraZeneca, Pfizer, Actelion, Speakers bureau: AbbVie, Bristol-Myers Squibb, Roche-Chugai, UCB, MSD, GSK, SOBI, Medac, Novartis, Janssen-Cilag, AstraZeneca, Pfizer, Actelion, X. Mariette Grant/research support from: Biogen, Pfizer, UCB, Consultant for: Bristol-Myers Squibb, LFB, Pfizer, GSK, UCB, H. Nüßlein Consultant for: AbbVie, Bristol-Myers Squibb, Celgene, Janssen, Lilly, MSD, Novartis, Pfizer, Roche, Speakers bureau: AbbVie, Bristol-Myers Squibb, Celgene, Janssen, Lilly, MSD, Novartis, Pfizer, Roche, M. Galeazzi: None declared, F. Navarro Grant/research support from: Pfizer, MSD, AbbVie, Bristol-Myers Squibb, Roche, Consultant for: Pfizer, MSD, Roche, UCB, AbbVie, Bristol-Myers Squibb, Jansen, Lilly, Speakers bureau: Pfizer, MSD, Roche, UCB, AbbVie, Bristol-Myers Squibb, M. Chartier Employee of: Bristol-Myers Squibb, Y. Elbez: None declared, C. Rauch Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, M. Le Bars Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb